PENGARUH TEKNOLOGI SISTEM INFORMASI KEUANGAN DAERAH TERHADAP KINERJA INDIVIDUAL DENGAN KEPERCAYAAN SEBAGAI VARIABEL MODERATING - Wulan Indah Lestari (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This research aimed to determine the effect of utilization of the financial information system technology to individual performance with trust as a moderating variable. The population in this study were 137 civil servants (PNS) on Sukoharjo regency sectors in which work on the part of the financial administration or accounting position. The sampling method used is purposive sampling, while samples that meet the criteria are 89 respondents. The questioner was examined by reliability and validity test, and then it went on classical assumption examination which consist of multicollinearity test, autocorrelation test, normality test and heteroscedasticity test. Then, Then, hypothesis test is done by t test. The result of this research indicate that the variable utilization of financial information systems technology significant positive effect on individual performance and trust variable moderate the effect of the use of financial information systems technology areas to individual performance. Keywords: Utilization of information technology, financial information system, trust, individual performance.